MENELAAH MODEL JUAL BELI EMAS SECARA KREDIT DI PEGADAIAN SYARIAH CABANG JOMBANG - Dimyati; Maulana, Kevin; Al-Azhar, M. Farid (TIJAROTANA : Jurnal Ekonomi Dan Bisnis Syariah, 2022)
Buying something on credit has become a way of life. Gold bullion is one product that is considered quite wise to be completed with a credit payment system. Islamic pawnshop is a financial institution that serves the sale and purchase of gold either in cash or installments in the form of products PRECIOUS. With descriptive-qualitative models, this shidy lead to the conclusion, (1) In the mechanism of buying and selling gold in Islamic pawnshop branches Jombang things enacted, among others: (a) Ai6rI used in buying and selling gold on credit is an agreement (b) In the implementation of Islamic pawnshop gold selling gold bought in cash to PT. Antam as a supplier to order customer. (c) Automatically goods commodity (gold precious metals) will serve as collateral for the repayment of the remaining debt to the Islamic pawnshop customers. After all client debt is paid off, then the precious metal gold along with the documents handed over to the customer. (2) Seen from the perspective of Islamic law the practice of bowing and selling gold on credit in Jombang Islamic pawnshop branches are in accordance with the Shari'ah, it is also corroborated by the fatwa DSN Number: 77 / DSP-MUI / V/2010 on the buying and selling of gold is not cash